Influence of the pulp of Mangifera indica and Myrciaria dubia on the bioactive and sensory properties of ice cream - Mauricio-Sandoval, Enrique Alonso; Espinoza-Espinoza, Luis Alfredo; Ruiz-Flores, Luis Alberto; Valdiviezo-Marcelo, Jaime; Moreno-Quispe, Luz Arelis; Cornelio-Santiago, Heber Peleg (Frontiers in Sustainable Food Systems, 2023)
Ice cream is widely consumed in the world. Unfortunately, its standard presentation is very poor in nutraceuticals; fruits such as Mangifera indica and Mayrciaria dubia have an important bioactive potential, which can be used to enrich this type of product in phytochemicals. However, it is still a subject of research to maintain the healthy and sensory aspects in the functionality of ice cream. The objective of this research is to study the influence of M. indica and M. dubia pulp on the total ascorbic acid content, total phenolic content, antioxidant capacity and sensorial. Four ice cream treatments were made containing Mangifera indica (15% and 20%) and Mirciaria dubia (5% and 10%). The content of ascorbic acid, total phenolic acid and antioxidant capacity were evaluated by applying an ordering test in addition to its sensorial analysis. The treatments with 10% of Myrciaria dubia showed the highest contents of ascorbic acid, total phenolic compounds and antioxidant capacity compared to the ice cream with 5%; while the influence of Mangifera indica regarding these parameters was relatively minor. However, sensory evaluation showed that T3 (5% Myrciaria dubia; 20% Mangifera indica) was the most preferred, surpassing the control ice cream. This demonstrates the importance of the addition of Mangifera indica from the sensory point of view, allowing a balance of sweet-acid flavor that is pleasant to the consumer while maintaining its healthy properties.